2008
DOI: 10.1086/521898
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Satiation: The Role of Categorization Level

Abstract: People usually like experiences less as they repeat them: they satiate. This research finds that people satiate less if they categorize the consumption episodes at lower levels. For instance, as people ate more jelly beans, their enjoyment declined less quickly when the candy was categorized specifically (e.g., cherry, orange) rather than generally (e.g., jelly bean). Three studies demonstrate this "specificity effect" for people's ratings of enjoyment both during and immediately after consumption. Process evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
190
1
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(217 citation statements)
references
References 33 publications
8
190
1
13
Order By: Relevance
“…Specifically, we find that recalling the varied experiences one has had in the past can have the inverse effect of reducing satiation and accelerating recovery for that item. Our work also differs from the few studies that have shown that subcategorization of consumption experiences can affect liking during repeated consumption (Raghunathan and Irwin 2001;Redden 2008). These prior works focused on preventing changes in liking before they happen, making particular aspects more salient during consumption, and considering fewer episodes from the past as relevant.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Specifically, we find that recalling the varied experiences one has had in the past can have the inverse effect of reducing satiation and accelerating recovery for that item. Our work also differs from the few studies that have shown that subcategorization of consumption experiences can affect liking during repeated consumption (Raghunathan and Irwin 2001;Redden 2008). These prior works focused on preventing changes in liking before they happen, making particular aspects more salient during consumption, and considering fewer episodes from the past as relevant.…”
Section: Discussionmentioning
confidence: 82%
“…Satiation during consumption varies as a function of how stimuli are categorized (Redden 2008), so it is reasonable to assume that the same may be true for recovering from satiation. In our second study, had we framed the decision not as that of listening to a favorite song but, rather, as doing something entertaining, then perhaps thoughts of television shows (our control condition) would also have helped people recover from satiation since they would fall into that category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, Redden (2008) demonstrated that when repeated consumption was subcategorized, feelings of satiation decreased. More specifically, when consumers perceive more components to a consumption experience, they perceive greater variability and thus experience less satiation.…”
Section: Disrupting Adaptation To Television Programsmentioning
confidence: 99%